2019
DOI: 10.1017/s181638312000017x
|View full text |Cite
|
Sign up to set email alerts
|

Living through war: Mental health of children and youth in conflict-affected areas

Abstract: Children in armed conflict are frequently deprived of basic needs, psychologically supportive environments, educational and vocational opportunities, and other resources that promote positive psychosocial development and mental health. This article describes the mental health challenges faced by conflict-affected children and youth, the interventions designed to prevent or ameliorate the psychosocial impact of conflict-related experiences, and a case example of the challenges and opportunities related to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…The current and growing body of literature on Rohingya refugee youth focuses upon their education ( Guglielmi et al, 2020b ), literacy ( Ali et al, 2020 ), mental health ( Frounfelker et al, 2019 ), and identity ( Bakali and Wasty, 2020 , Oosterom et al, 2019 ). In exploring identity, a qualitative case study elucidates the experiences of two Rohingya refugee boys in Malaysia who, in light of being legally unrecognized as refugees, utilize linguistic and social capital through performing patriotism and assimilating to local culture to cultivate a sense of belonging ( Lee, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The current and growing body of literature on Rohingya refugee youth focuses upon their education ( Guglielmi et al, 2020b ), literacy ( Ali et al, 2020 ), mental health ( Frounfelker et al, 2019 ), and identity ( Bakali and Wasty, 2020 , Oosterom et al, 2019 ). In exploring identity, a qualitative case study elucidates the experiences of two Rohingya refugee boys in Malaysia who, in light of being legally unrecognized as refugees, utilize linguistic and social capital through performing patriotism and assimilating to local culture to cultivate a sense of belonging ( Lee, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies evaluating mental health found that over half of Rohingya youth in Bangladesh between the ages of 2 and 16 experience emotional and peer problems ( Khan et al, 2019 ) and nearly 97% of all participants screened positive on measures of emotional distress ( Shaw et al, 2019 ) in Malaysia. Rohingya refugee youth reveal social and psychological difficulties due to non-Western conceptualizations around mental health experiences ( Frounfelker et al, 2019 ), calling for interventions with cultural salience that display the protective nature of religion and its positive contribution to meaning making. A qualitative study exploring psychological difficulties of eight Rohingya refugee youth due to forced migration through non-directed sand play therapy revealed risk factors of death and fighting, but also displayed resilience through picture narratives of survival on boats and pictures of permanence through creating schools and safe space ( Lee & Jang, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…За таких умов під впливом стресових факторів у дітей молодшого шкільного віку значно знижується апетит, з'являються скарги на абдомінальний біль, цефалгії. У підлітковому віці відзначається недовіра до оточуючого світу, виникає поведінка заперечення, бунтарське поводження [9,10]. Усе це, безумовно, дуже негативно впливає на формування харчових звичок у дітей та сприяє розвитку патологічних відхилень у ХП.…”
Section: резюме актуальність проблемі харчування як ключовому фактору...unclassified
“…On February 24, Russian weapons began indiscriminate shelling of Ukrainian cities. Similarly to the pandemic in which children and elderly were most vulnerable, in time of war they are vulnerable too (Frounfelker et al , 2019; Gavin et al , 2020). Listening to teen stories, understanding their experiences is the first step in developing strategies to help them cope with traumatic consequences of war.…”
Section: Introductionmentioning
confidence: 99%